Recent developments in the application of microwave energy in process metallurgy at KUST - Shaohua, Ju; Singh, Pritam; Jinhui, Peng; Nikoloski, Aleksandar N.; Chao, Liu; Shenghui, Guo; Das, R.P.; Libo, Zhang (Mineral processing and extractive metallurgy review, 2018)
Kunming University of Science and Technology (KUST) has successfully developed, designed, fabricated and installed industrial microwave units for (i) removal of halides, (ii) activation of carbon, (iii) heating of dust laden air in electrostatic precipitators, (iv) drying of water based paints, and (v) heating of the HF pickling solution for cold rolled titanium alloy coils. This review article provides a summary of these process metallurgy applications. It is found that the use of microwave energy can increase the process efficiency, giving advantages, such as lower reaction temperature and shorter reaction time compared to traditional processes. 可显著降低反应温度、缩短时间，具有强化作用